A Dictionary And Grammatical Sketch Of Ruruuli-Lunyala - Saudah, Namyalo; Witzlack-Makarevich, Alena; Kiriggwajjo, Anatole; Atuhairwe, Amos; Molochieva, Zarina; Mukama, Ruth; Zellers, Margaret (My University, 2021)
This book is a dictionary and grammatical sketch of Ruruuli-Lunyala, a Great Lakes Bantu language spoken by over 200,000 people in central Uganda. The dictionary part includes about 10,000 entries. Each entry provides translations into English, example sentences, and essential grammatical information. The dictionary part is supplemented with a grammatical sketch of Ruruuli-Lunyala. It treats a wide range of central phonological and morpho-syntactic topics. This book is a result of a joined effort of a large team of linguists and many speakers of Ruruuli-Lunyala and is intended as a resource for linguists and Ruruuli-Lunyala speakers, learners, and educators.
Keywords: Ruruuli-Lunyala; HUMANITIES and RELIGION::Languages and linguistics::Other languages::Bantu languages; Dictionary